Postcolonial Biology : Psyche and Flesh after Empire - Bahri, Deepika, 1962- (Book collections on Project MUSE., 2017)
Although the body has been a vast subject for postcolonial studies, few theorists have attempted to go beyond the simple mixing of races in examining the impact of colonialism on the colonized body. However, as Deepika Bahri argues, it is essential to see the postcolonial body in a variety of forms: as capable of transformation not only in psyche and outward behavior but also in flesh and blood. European colonizers brought new ways of seeing the body in matters as basic as how to eat, speak, sit, shit, or spit. As nations decolonized, these imperialistic ideas remained, becoming part of the global economy of the body. In Postcolonial Biology, Bahri argues that the political challenges of the twenty-first century require that we deconstruct these imperial notions of the body, as they are fundamental to power structures governing todays globalized world. Postcolonial Biology investigates how minds and bodies have been shaped by colonial contact, to create deeply embedded hierarchies among the colonized. Moving beyond North/Souththinking, Bahri reframes the questions of postcolonial bodies to address all societies, whether developed or developing. Engaging in innovative, highly original readings of major thinkers such as Adorno, Horkenheimer, Derrida, and Fanon, this book brings an important new focus to the field of postcolonial studies-one that is essential to understanding the ideas and conflicts that currently dominate the global order.